ChemInform Abstract: 1, 3‐Dipolar Cycloaddition Reactions of Indan‐1‐one Enamines Across Arylnitrile Oxides Leading to Novel Cyclic Isoxazoline Derivatives. Issue 36 (9th September 2014) - Jelizi, Hanene; Wannassi, Nadia; El Baker Rammah, Mohamed; Ciamala, Kabula; Knorr, Michael; Rousselin, Yoann; Kubicki, Marek M.; Strohmann, Carsten; Enescu, Mironel
Abstract A series of cyclic fused‐isoxazolines is obtained by regioselective and diastereoselective 1, 3‐dipolar cycloaddition of enamines (I) and (IV) to arylnitrile oxides.